Indicators for Measuring Performance of Financial Cooperatives in Nepal (Journal of Business and Management Research, 2017)
Comprehensive institutional assessment tool helps to appraise performance of an organization and adopt appropriate strategies for enhancing performance. Different organizations demand different indicators and standards for appraising performance. Different tools such as PEARLS and CAMEL have been prescribed measure performance of financial institutions. These tools were developed in different contexts and are not adopted in Nepali cooperative sector. The objective of this paper is to identify and recommend different indicators for measuring performance of financial cooperatives in Nepal. Expert interviews and focus group discussions were applied to explore the indicators for performance assessment. The identified indicators were piloted with randomly selected 210 cooperatives. The findings showed that 32 financial ratios under eight performance measurement dimensions and 25 self-governance related indicators are needed to assess the performance of financial cooperatives in Nepal and elsewhere. Implications of the findings are discussed and limitations of the study are highlighted,